1992
DOI: 10.1143/jjap.31.4465
|View full text |Cite
|
Sign up to set email alerts
|

Focused Ion Beam Assisted Etching of Quartz in XeF2 without Transmittance Reduction for Phase Shifting Mask Repair

Abstract: The gauge-links connecting the parton field operators in the hadronic matrix elements appearing in the transverse momentum dependent distribution functions give rise to T -odd effects. Due to the process-dependence of the gauge-links the T -odd distribution functions appear with different prefactors. A consequence is that in the description of single spin asymmetries the parton distribution and fragmentation functions are convoluted with gluonic pole cross sections rather than the basic partonic cross sections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…In the FIB-GAE process, the FIB is used to initiate a chemical reaction between the substrate surface and XeF 2 gas molecules absorbed to allow the material to be volatilized locally and pumped away. The major advantages of FIB-GAE over FIB milling are higher material removal rates and lower redeposition [14,15]. The Si material redeposited on the FIB milling result's surface reacts with XeF 2 gas and the product is volatilized locally and pumped away during FIB-GAE, as shown in figure 12.…”
Section: Micro/nano-structure Fabrication By Fibi and Fib Xef 2 -Assi...mentioning
confidence: 99%
“…In the FIB-GAE process, the FIB is used to initiate a chemical reaction between the substrate surface and XeF 2 gas molecules absorbed to allow the material to be volatilized locally and pumped away. The major advantages of FIB-GAE over FIB milling are higher material removal rates and lower redeposition [14,15]. The Si material redeposited on the FIB milling result's surface reacts with XeF 2 gas and the product is volatilized locally and pumped away during FIB-GAE, as shown in figure 12.…”
Section: Micro/nano-structure Fabrication By Fibi and Fib Xef 2 -Assi...mentioning
confidence: 99%
“…A positive gallium (Ga þ ) ion beam was used to etch nanometer patterns with xenon difluoride (XeF 2 ) enhanced etching gas. [36][37][38][39][40][41][42][43][44] Figure 2(b) shows an array of Fresnel circular gratings with about 1 mm spacing. With this tiny size and gap distance, 10,000 Fresnel circular gratings can be fabricated within a 10 × 10 cm 2 area.…”
Section: Fabrication Of Fresnel Circular Gratingsmentioning
confidence: 99%
“…It is well known that LN is chemically inert to etching. It has been shown that Xenon Difluoride (XeF 2 ) assisted FIB milling of Si [12] and Quartz [13,14] enhances the milling quality in terms of conicity and depth. XeF 2 can increase the material removal rate by reducing the re-deposition effects and by more efficient chemical etching.…”
Section: D Photonic Crystal Design Fabrication and Simulationsmentioning
confidence: 99%